Hubungan Efikasi Diri dengan Tingkat Kecemasan dalam Menghadapi Ujian Blok pada Mahasiswa Tahun Pertama Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Kadek Ananda Pratama Putra; Putu Asih Primatanti; Ni Putu Diah Witari (Aesculapius Medical Journal, 2023)
Self-efficacy is an individual's belief in his ability to manage the situation experienced. Situations that often occur when facing exams are anxiety that occurs because of psychological and intrapsychic responses. The purpose of the study was to find out how the relationship between self-efficacy and level of anxiety in facing exams in early-level students of the Faculty of Medicine and Health Sciences, Warmadewa University. This study uses a correlational analytic with cross- sectional approach. The method of collecting data on respondents' self-efficacy was using the General Self Efficacy (GSE) questionnaire technique and the anxiety in facing the block exam was using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Samples were analyzed using univariate and bivariate analysis techniques. It was found that respondents who did not experience anxiety in facing the block exam were 61.3%, those who experienced mild anxiety in facing the block exam were 18.7%, 9%, severe 9.7%, and very severe 1.3%. Respondents who have a very high level of self-efficacy 14.2%, high 85.2%, low 0.6%, and very low 0%. The p- value of this study is 0.000. Because the value (p) 0.00 <0.05, which indicates that there is a significant relationship between self-efficacy and anxiety levels. The value obtained is -0.612 which indicates the strength of its strength. This means that there is a relationship between self- efficacy and facing examinations for early-level students of the Faculty of Medicine and Health Sciences, Warmadewa University